PERANCANGAN DAN PENERAPAN PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK-ETAP PADA USAHA MIKRO KECIL MENENGAH (Studi Kasus pada Perajin Shuttlecock Yunda di Pringgolayan Tipes Surakarta) - Riski Ambarwati, Djoko Kristianto & Muhammad Rofiq Sunarko (Universitas Slamet Riyadi, 2017)
The presence of Financial Accounting Standards Entities without PublicAccountability (SAK ETAP) is expected to provide facilities for small businesses inpresenting the financial statements. The problem in this research is: How does thedesign and preparation of the format of the financial statements of craftsmenShuttlecock Yunda in Pringgolayan Tipes Surakarta based SAK ETAP The purposeof this study is to describe the design and preparation of the format of the financialstatements of craftsmen Shuttlecock Yunda in Pringgolayan tipes Surakarta basedSAK ETAP. This study uses a case study on Craftsmen Shuttlecock PringgolayanTipes Yunda in Surakarta. The data used is qualitative data and kunatitatif. The datasource using primary data and secondary data. The technique of collecting datausing interviews, observation and documentation. Data were analyzed usingdescriptive analysis is based on interviews, observation and document analysis.Based on the results of research conducted on the design and preparation of theformat of the financial statements of craftsmen Shuttlecock Yunda in PringgolayanTipes Surakarta based SAK ETAP, it can be concluded as follows: The preparationof the balance sheet based SAK-ETAP done by including all assets, liabilities andcapital owned by craftsmen shuttlecock Yunda in Pringgolayan Tipes Surakarta.Assets owned by craftsmen Shuttlecock Yunda includes current assets and noncurrentassets, liabilities contains information about short-term debt and long-termdebt, while equity capital consists of the owner. Income Statement prepared inaccordance with GAAP ETAP as references used to prepare the financial statementson small and medium businesses. An income statement prepared for craftsmenShuttlecock Yunda researchers contains information on total sales, sales returns, andloads of operational activities, so as to know the amount of net income, while the taxburden is not included, since craftsmen Shuttlecock Yunda not have a TIN. Statementof Changes in Equity is a report that shows changes in capital in the same period.Changes in equity prepared by researchers for craftsmen Shuttlecock Yundaprovides information on the capital earlier in the year, plus income earned andreduced by prive, so the final amount obtained is the amount of capital owned bycraftsmen at the end of the period.Keywords: Financial Accounting Standards Entities without Public Accountability.